The Bush Harvest in Pinehouse, Saskatchewan, Canada - Tobias, Terry N.; Kay, James J. (ARCTIC, 1994)
Hunting, trapping, fishing and gathering provide an important source of food and fuel for the Cree-speaking Metis of Pinehouse on the Churchill River in northern Saskatchewan. This paper reports the findings of a harvest survey based on one-year recall. The village's total harvest of fish, mammals, birds, berries, and fuelwood is documented by species from April 1983 through March 1984. Virtually all 145 adult male residents were interviewed. Respondents reported their harvest in units of their choice such as fish tub and truckload of fuelwood. Studies based on participant observation, monitoring programs involving short recall periods of a few days, and empirical measurement were done to determine conversion factors. These were used to translate harvesters' reporting units into numbers of animals by species (cords for fuelwood), and then to whole and edible weights. The total harvest was 84.5 tonnes of edible meat or 0.342 kg per day for each of the 676 residents. Three tonnes of berries and 682 cords of fuelwood were harvested. The village's gross income for the survey period is assessed and a dollar value assigned to the harvest. The bush harvest (income-in-kind and commodities) accounted for one-third of total village income, which contradicts the prevalent stereotype that resources from the land do not significantly contribute to the Pinehouse economy.Key words: native harvest survey, northern Saskatchewan Métis, subsistence harvests, domestic fisheries, subarctic village economy La chasse, le piégeage, la pêche et la cueillette fournissent une importante source de nourriture et de combustible pour les Métis de langue cri habitant Pinehouse sur la rivière Churchill, dans le nord de la Saskatchewan. Dans cet article, on rapporte les relevés des prises en se fondant sur le rappel d'une année. On donne par espèces le total des prises effectuées d'avril 1983 à mars 1984 pour le poisson, les mammifères, les oiseaux ainsi que les baies et le bois à brûler. Pratiquement tous les 145 résidents adultes de sexe ...